Identification of citrullinated peptides in the synovial fluid of patients with rheumatoid arthritis using LC-MALDI-TOF/TOF. Issue 9 (September 2016) - Wang, Fei; Chen, Fang-Fang; Gao, Wen-Bo; Wang, Hai-Yong; Zhao, Ning-Wei; Xu, Min; Gao, De-Yu; Yu, Wei; Yan, Xiao-Ling; Zhao, Jian-Ning; Li, Xiao-Jun
Abstract The objective of the study is to investigate potential citrullinated autoantigens as targets of anti-citrullinated protein antibodies (ACPAs) response in synovial fluids (SFs) of patients with rheumatoid arthritis (RA). SFs from six RA patients and six osteoarthritis (OA) patients as controls were collected. The citrullinated proteins in SFs were extracted by immunoprecipitation with rabbit anti-citrulline antibodies. Matrix-assisted laser desorption/ionization time of flight mass spectrometry/time of flight mass spectrometry (MALDI-TOF/TOF) mass spectrometry was subsequently performed to discover a characteristic neutral loss to finally determine citrullinated autoantigens. A total of 182 citrullinated peptides and 200 citrullinated sites were identified in RA SFs, while 3 citrullinated peptides and 4 citrullinated sites were identified in OA SFs. The 182 citrullinated peptides from RA SFs and the 3 citrullinated peptides from OA SFs were derived from 83 and 3 autoantigens, respectively. Eighty-three autoantigens except protein-arginine deiminase type-2 (PADI2) and protein-arginine deiminase type-2 (PADI4) were over-citrullinated compared with controls, and the citrullinated sites of PADI2 and PADI4 were different in two groups. Interestingly, citrullinated histone H3.3 (H3F3A) was found in OA controls, but not in RA groups. The differential citrullinated proteins identified in RA SFs suggested potential autoantigens were targeted for ACPAs response and might contribute to the induction and perpetuation of complement activation and joint inflammation in RA.